2018
DOI: 10.1002/bjs5.78
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the stage of innovation of biological mesh for complex or contaminated abdominal wall closure

Abstract: BackgroundAchieving stable closure of complex or contaminated abdominal wall incisions remains challenging. This study aimed to characterize the stage of innovation for biological mesh devices used during complex abdominal wall reconstruction and to evaluate the quality of current evidence.MethodsA systematic review was performed of published and ongoing studies between January 2000 and September 2017. Eligible studies were those where a biological mesh was used to support fascial closure, either prophylactica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 63 publications
0
24
0
1
Order By: Relevance
“…9 Some retrospective case-series have suggested that biological meshes can be safely used in complex and contaminated settings; 5,9 high quality or randomised evidence is however absent and so they are not used routinely in this setting. 10 Prophylactic biological mesh implantation at time of stoma closure (to prevent incisional hernia) has not been tested in multicentre randomised studies. 10 The IDEAL framework describes a pathway for testing surgical devices and innovation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Some retrospective case-series have suggested that biological meshes can be safely used in complex and contaminated settings; 5,9 high quality or randomised evidence is however absent and so they are not used routinely in this setting. 10 Prophylactic biological mesh implantation at time of stoma closure (to prevent incisional hernia) has not been tested in multicentre randomised studies. 10 The IDEAL framework describes a pathway for testing surgical devices and innovation.…”
Section: Introductionmentioning
confidence: 99%
“…10 Prophylactic biological mesh implantation at time of stoma closure (to prevent incisional hernia) has not been tested in multicentre randomised studies. 10 The IDEAL framework describes a pathway for testing surgical devices and innovation. 11 We described proof of concept in a single case (stage 1), 12 development in a short case series (stage 2A), exploration within a feasibility randomised trial (stage 2B), 13 and here describe assessment within a phase 3 randomised controlled trial (stage 3).…”
Section: Introductionmentioning
confidence: 99%
“…The direct advantages of biological mesh hence remain unproven despite their widespread usage. 11 Low-level evidence and opinion has inferred that biologic meshes are superior to synthetic prosthetic meshes in repairing complex and contaminated abdominal wall defects, including work published by our own group, 3,4,8,9,12,13 but long-term data on the safety and durability of biologic mesh in infected fields remains limited. A retrospective study by Rosen and colleagues reported an overall wound complication rate of 48% when biologic mesh was used in contaminated or complex abdominal fields using a single-staged approach.…”
Section: Discussionmentioning
confidence: 99%
“…The main disadvantage is the high costs which go along with these biological meshes. Therefore, the meshes are mostly applied in the infectious situs after the explantation of an infected conventional mesh [ 11 ].…”
Section: Discussionmentioning
confidence: 99%